IoT-Based Monitoring for Optimizing Yield of Gogo Rice (Oryza sativa, L.) - Handayani, Etik Puji; Saputri, Tri Aristy; Sutomo, Budi (Universitas Dharma Wacana, 2025)
Advancements in Internet of Things (IoT) technology have introduced new opportunities in precision agriculture, particularly for enhancing the productivity of upland rice (Oryza sativa, L.) cultivated on marginal lands. This study aims to integrate an IoT-based monitoring system with the application of biochar and Trichoderma harzianum to optimize soil parameters and water resource efficiency. The monitoring system utilizes Trico Master and Slave devices to measure real-time environmental parameters, including soil pH, soil moisture, soil temperature, and air temperature. The results reveal that the application of biochar at a dosage of 1 kg/m² increased soil pH from an average of 7.0 to 8.7, creating a conducive environment for the activity of Trichoderma harzianum. This microorganism demonstrated its ability to improve soil quality by decomposing organic matter and enhancing nutrient absorption by plants. Additionally, the IoT-based automated irrigation system maintained soil moisture levels above 45% while reducing water usage by up to 30% compared to manual irrigation methods. In conclusion, the integration of IoT technology with biochar and Trichoderma harzianum significantly improved upland rice yield, resource efficiency, and the sustainability of agricultural systems. This study presents an innovative and sustainable approach to supporting future food security, particularly in resource-limited environments